2016
DOI: 10.1021/acsami.6b05232
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Textile: Enzyme Encapsulated Layer-by-Layer Structural Proteins

Abstract: Self-healing materials, which enable an autonomous repair response to damage, are highly desirable for the long-term reliability of woven or nonwoven textiles. Polyelectrolyte layer-by-layer (LbL) films are of considerable interest as self-healing coatings due to the mobility of the components comprising the film. In this work mechanically stable self-healing films were fabricated through construction of a polyelectrolyte LbL film containing squid ring teeth (SRT) proteins. SRTs are structural proteins with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 48 publications
(85 reference statements)
1
48
0
Order By: Relevance
“…The amino acid sequence of proteins determines their secondary and tertiary structures; hence they provide a variety of structural conformations . Proteins can often self‐assemble in order to form natural materials with extraordinary properties such as extremely high durability or elasticity . Hence, designing new proteins using biotechnology tools has been an interest for materials scientists for modifying and assembling novel morphologies and molecular architectures .…”
Section: Protein‐based 2d Nanocompositesmentioning
confidence: 99%
“…The amino acid sequence of proteins determines their secondary and tertiary structures; hence they provide a variety of structural conformations . Proteins can often self‐assemble in order to form natural materials with extraordinary properties such as extremely high durability or elasticity . Hence, designing new proteins using biotechnology tools has been an interest for materials scientists for modifying and assembling novel morphologies and molecular architectures .…”
Section: Protein‐based 2d Nanocompositesmentioning
confidence: 99%
“…17 The self-healing fabrics with healing coating technology, which was inspired by the self-healing proteins in squid ring teeth, would be one of the exceptional discoveries through the bottom-up process of biomimicry. Gaddes et al 18 reported that the squid ring teeth (SRT) proteins comprised with semi-crystalline construction, flexible and rigid structure and high elastic modulus that contributing towards the properties of self-repairing. During the investigation, a polyelectrolyte film with SRT proteins had been applied onto a torn area of a textile surface as a self-repairing coating.…”
Section: Self-healing Textiles By Coatingmentioning
confidence: 99%
“…Preparation of enzyme-containing polyelectrolyte microcapsules. Polyelectrolyte microcapsules with urease were produced by the method of alternate layer-by-layer adsorption with the application of polystyrene sulfonate (PSS) and polyallylamine hydrochloride (PAAH) molecules to composite calciumcarbonate spherulites containing urease as described in [4][5][6]8].…”
Section: а в сmentioning
confidence: 99%